2011
DOI: 10.1111/j.1745-459x.2011.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Various Sweeteners in Petit Suisse Cheese: Determination of the Ideal and Equivalent Sweetness

Abstract: For a sweetener to successfully replace sucrose in food formulations, studies must first determine the necessary concentration of the sweetener to be used and its equivalent sweetness to sucrose. In this study, we verified both the equivalent sweetness and the magnitude of sweetness of processed cheese sweetened with different sweeteners and combinations of sweeteners. A total of four formulations were evaluated: sucralose, sucralose/acesulfame‐K (4:1), thaumatin/sucralose (2:1) and cyclamate/saccharin (1:1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 25 publications
0
59
1
1
Order By: Relevance
“…Further research exploring higher concentrations is necessary. In this sense, it is important to stress that although thaumatin has been claimed to be 2000 to 5000 sweeter than sucrose (Glória, 2003), more recent research has shown that its sweetness potency is about 500 times lower than that of sucralose (Cadena & Bolini, 2012;De Souza et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Further research exploring higher concentrations is necessary. In this sense, it is important to stress that although thaumatin has been claimed to be 2000 to 5000 sweeter than sucrose (Glória, 2003), more recent research has shown that its sweetness potency is about 500 times lower than that of sucralose (Cadena & Bolini, 2012;De Souza et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The procedures followed in each stage was based on the work of Souza et al (2011). To reach the equivalent saltiness for the various salt replacements relative to the salt taste of sodium chloride in butter, sensory evaluations were conducted at various stages.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The panellists selected were trained to use magnitude scales according to Souza et al (2011). The panellists selected were trained to use magnitude scales according to Souza et al (2011).…”
Section: Selection Of Panellistsmentioning
confidence: 99%
See 1 more Smart Citation
“…To successfully substitute sucrose for sweeteners in food formulations, preliminary studies must be carried out to determine the concentrations of sweeteners to be used and its equivalent sweetness as compared to sucrose (Souza et al, 2011). For that, the magnitude estimation method is used among others methodologies (Cardoso & Bolini, 2007).…”
Section: Introductionmentioning
confidence: 99%